Anisotropically Stiff 3D Micropillar Niche Induces Extraordinary Cell Alignment and Elongation. Issue 15 (18th May 2016) - Alapan, Yunus; Younesi, Mousa; Akkus, Ozan; Gurkan, Umut A.
Abstract : A microfabricated pillar substrate is developed to confine, align, and elongate cells, allowing decoupled analysis of stiffness and directionality in 3D. Mesenchymal stem cells and cardiomyocytes are successfully confined in a 3D environment with precisely tunable stiffness anisotropy. It is discovered that anisotropically stiff micropillar substrates provide cellular confinement in 3D, aligning cells in the stiffer direction with extraordinary elongation.